SISTEM INFORMASI PENYEDIAAN ATK PADA STMIK PELITA NUSANTARA MEDAN - Rita Hamdani (Journal Of Informatic Pelita Nusantara, 2019)
Information is not only needed by the community, but also companies, one of which is a company engaged in the field of education, namely STMIK Pelita Nusantara Medan. There is a lot of information in STMIK Pelita Nusantara Medan. Information about education, be it about students, lecturers, lecturer performance, information on student activities and lecturer Information has been based online. But not all information contained in STMIK Pelita Nusantara Medan is based online or database based. One of them is information about the use of ATK information, ATK management still uses Microsoft Excel applications. Management of ATK with Microsoft Excel has disadvantages such as, data entered using sheets, with the amount of data when using sheets, it can make the ATK management section experiencing difficulties. Difficulties can be in the form of difficulty in finding the data needed, must use a formula that must be typed, the difficulty of making monthly reports to find out ATK expenditure. So it is difficult to make decisions in the management of ATK supplies. To facilitate the management of ATK inventory, a database-based application is needed. This research was made using Visual Basic. Net applications and the database used was SQL Server..